Pembentukan Portofolio Optimal dengan Model Markowtz dan Two-Fund Theorem pada Saham LQ-45 di Bursa Efek Indonesia - Febriani Febriani; Media Rosha (UNIVERSITAS NEGERI PADANG, 2020)
bstract — Inflation is an increase in the level prices continually. The impact of inflation can beovercome by investing capital or resources carried in an asset with the expectation of obtaining profits in the future which is called investment. Portfolio is a set of several assets to reduce of risk. One of the way to form an optimal portfolio is Markowitz Model using Two-Fund Theorem that can present a portfolio of the smallest risk according to investor preferences. The purpose of this research is to determine the composition of optimal portfolio and proportion of fund from each stock in optimal portfolio.This research used secondary which is consist of 42 samples in LQ-45 during February-July 2019. The result of analysis 42 samples there are 7 stock to form an optimal portfolio with the proportion of them. They are BBRI 43.91%, BRPT 24.08%, EXCL 14.75%, INTP 0.35%, JSMR 8.75%, MNCN 3.57%, WIKA 4.59%.Keywords — optimal portfolio, markowitz model, two-fund theorem.